Analysis of the driving path of e-commerce to high-quality agricultural development in China: empirical evidence from mediating effect models - Kong, Yanfang; Zhang, Xue; Li, Xiaoxu; Pastpipatkul, Pathairat; Liu, Jianxu; Feng, Chuhui (Frontiers in Sustainable Food Systems, 2024)
Purpose This study investigates the impact of e-commerce on high-quality agricultural development (HQAD) in China. As the agricultural sector transitions towards higher quality production in the digital era, understanding the influence pathways and mechanisms of e-commerce becomes crucial. We aim to quantify this influence through a hierarchical approach. Methods Utilizing provincial panel data from 2000 to 2021, we construct a comprehensive HQAD evaluation system using the entropy method. Parallel mediating effect models are employed to empirically assess the multi-level effects of e-commerce on HQAD. Results Benchmark regression analyzes reveal a significant positive effect of e-commerce on HQAD, indicating its role as a key driver in China’s agricultural advancement. Mechanism tests identify several intermediary pathways through which e-commerce indirectly promotes HQAD, including market expansion, agricultural value chain optimization, enhanced social services, and improved infrastructure. Notably, market expansion and value chain optimization demonstrate the most substantial mediation effects, accounting for 43.27 and 14.18% of the total effect, respectively. Discussion This research contributes to the literature by establishing a comprehensive HQAD evaluation framework, providing a theoretical foundation for future studies. By incorporating circulation factors into the production system, we elucidate the complex influence mechanisms of e-commerce on agricultural production, addressing a significant research gap. Furthermore, we propose a novel “demand-driven supply optimization” paradigm, offering valuable insights for policy formulation aimed at fostering HQAD in China.